Transient Neonatal Diabetes Mellitus followed by recurrent asymptomatic hypoglycaemia: a case report. Issue 1 (December 2015) - Priyadarshi, Archana; Verge, Charles; Vandervliet, Leah; Mackay, Deborah; Bolisetty, Srinivas
Abstract Background Transient Neonatal Diabetes Mellitus is the commonest cause of diabetes presenting in the first week of life. Majority of infants recover by 3 months of age but are predisposed to developing type 2 diabetes later on in life. This condition is usually due to genetic aberrations at the 6q24 gene locus, and can be sporadic or inherited. This disorder has three phases: neonatal diabetes, apparent remission, relapse of diabetes. Case Presentation Our case, a neonate presented with low birth weight and growth retardation along with the metabolic profile consistent with transient diabetes mellitus at birth. We report a novel clinical observation of recurrent asymptomatic hypoglycaemia detected on pre-feed blood glucose level monitoring in our case with transient neonatal diabetes mellitus at 6 weeks of age, 4 weeks after the remission of diabetes mellitus. Conclusion This case demonstrates that neonates in remission following transient diabetes mellitus can present with recurrent asymptomatic hypoglycaemia without any other obvious congenital malformations seen. This asymptomatic hypoglycaemia may persist for weeks and may be missed if pre-feed blood glucose level monitoring is not done in these infants. Also, these infants may require an aggressive enteral feeding regimen with high glucose delivery rate to maintain normoglycemia.